1976
DOI: 10.1073/pnas.73.12.4449
|View full text |Cite
|
Sign up to set email alerts
|

Binding of triton X-100 to diphtheria toxin, crossreacting material 45, and their fragments.

Abstract: Binding of the nonionic detergent [3HrTriton X-100 by diphtheria toxin, by the nontoxic serologically related protein crossreacting material (CRM) 45, and by their respective A and B fragments has been studied. If Fragment A then catalyzes the transfer of the ADP-ribosyl group from NAD+ to elongation factor 2 (EF-2), thereby causing its inactivation (1, 2).Previous studies (3, 4) with mammalian cell cultures have shown that each sensitive cell carries about 4000 specific surface membrane receptors that initi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
63
1

Year Published

1981
1981
2005
2005

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(65 citation statements)
references
References 16 publications
1
63
1
Order By: Relevance
“…Different experimental approaches have indicated that at low pH DT becomes hydrophobic and inserts into the lipid bilayer [21,[24][25][26][27]. As shown in fig.2, at pH 4.5 all toxins induce a very large change in turbidity that may be related to liposome aggregation and/or fusion.…”
Section: Resultsmentioning
confidence: 99%
“…Different experimental approaches have indicated that at low pH DT becomes hydrophobic and inserts into the lipid bilayer [21,[24][25][26][27]. As shown in fig.2, at pH 4.5 all toxins induce a very large change in turbidity that may be related to liposome aggregation and/or fusion.…”
Section: Resultsmentioning
confidence: 99%
“…Whether or not the phenomenon by itself is involved in the translocation process has not been elucidated. Diphtheria toxin, which requires an acidic environment for internalization [14,15], was found to induce fusion of DPPC vesicles only at acidic pH [ 161. Recently, from several experimental results [5,7,14], it' was proposed that the acidic environment might not be required for ricin internalization.…”
Section: Effect Of the A-chain On The Membrane Mixing Of Dmpc And Dppmentioning
confidence: 99%
“…In a second step, DT is endocytosed in clathrincoated vesicles (Moya et a/., 1985;Morris et a/., 1985). In an endosomal compartment, the translocation domain (T: molecular mass 20 kDa) at the amino-terminal end of DTB (Boquet et al, 1976) facilitates the transport of the catalytic domain (C or DTA: molecular mass 21 kDa) to the cytosol. In the third step, the C domain ADP-ribosylates and subsequently inactivates elongation factor 2 (EF2) (Collier, 1967;Honjo et a/., 1968;Gill et a/., 1969), leading to cell death.…”
Section: Introductionmentioning
confidence: 99%